Rare Complication of Pneumomediastinum and Pneumopericardium in a Patient with COVID-19 Pneumonia - Anshika Singh; Jessica Bass; David H. Lindner (Case Reports in Pulmonology)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a recently discovered coronavirus which has caused a global outbreak of severe pneumonia with complications leading to hypoxic respiratory failure, acute respiratory distress syndrome (ARDS), cytokine storm, disseminated intravascular coagulation (DIC), and even gastrointestinal symptoms. While ground-glass opacity (GGO) is a typical radiographic finding associated most frequently with COVID-19 pneumonia, other less commonly noted atypical radiographic lung features include isolated lobar or segmental consolidation without GGO, discrete small nodules (centrilobular, “tree-in-bud”), lung cavitation, and smooth interlobular septal thickening with pleural effusion. Pneumomediastinum in COVID-19 patients has rarely been reported. A finding of pneumopericardium is unusual too. This report discusses the case of a young male with COVID-19 pneumonia who was found to have both these features on computed tomographic (CT) scans of his chest on presentation.